Challenges And Obstacles To The Application Of Restorative Justice On The Criminal Justice System In Indonesia - Tri Wibowo, Kurniawan; ., Sunarko (International Journal of Law Policy and Governance, 2023)
The practice of enforcing the law of restorative justice, as an out-of-court settlement mechanism based on the principle of justice, has also been reflected in several court decisions. Challenges and obstacles to the application of restorative justice in the criminal justice system in Indonesia are the settlement of cases in the spirit of restorative justice, must be the ability to find a fair and mutually beneficial solution ( win-win solution ) for both parties, both victims and perpetrators. The admission of guilt of the perpetrator of a crime is a prerequisite for restorative justice. Based on these challenges and obstacles, it is necessary to regulate the laws and regulations governing the implementation of restorative justice, the existence of an element of confession of guilt from the perpetrators of the crime as a prerequisite for restorative justice